Microcontrollers fundamentals for engineers and scientists - Barrett, Steven F. (Steven Frank), 1957-; Pack, Daniel J. (San Rafael, Calif. : Morgan & Claypool, 2006)
This book provides practicing scientists and engineers a tutorial on the fundamental concepts and use of microcontrollers. Today, microcontrollers, or single integrated circuit (chip) computers, play critical roles in almost all instrumentation and control systems. Most existing books are written for undergraduate and graduate students taking an electrical and/or computer engineering course. Furthermore, these texts have been written with a particular model of microcontroller as the target discussion. These textbooks also require a requisite knowledge of digital design fundamentals. This textbook presents the fundamental concepts common to all microcontrollers. Our goals are to present the over-arching theory of microcontroller operation and to provide a detailed discussion on constituent subsystems available in most microcontrollers. With such goals, we envision that the theory discussed in this book can be readily applied to a wide variety of microcontroller technologies, allowing practicing scientists and engineers to become acquainted with basic concepts prior to beginning a design involving a specific microcontroller. We have found that the fundamental principles of a given microcontroller are easily transferred to other controllers. Although this is a relatively small book, it is packed with useful information for quickly coming up to speed on microcontroller concepts.
Digital design fundamentals -- Introduction -- Binary math -- Representation of integers and floating point variables -- Two's complement -- Floating point notation -- Basic math operations: Addition and subtraction -- Codes -- Unicode and ASCII -- Gray code -- Combinational and sequential circuits -- Digital design building blocks -- Digital design solutions -- Programmable gate arrays -- Microprocessors -- Digital signal processors (DSPs) -- Microcontrollers -- Mixed mode processing microcontroller with FPGA -- Summary -- The design and development process -- The design process -- Implementation and testing tools -- Software development process -- Summary -- Microcontroller -- So what exactly is a microcontroller -- Microcontroller overview -- Basic architecture -- RISC versus CISC instruction set -- Register set -- Bus structure -- Address bus -- Data bus -- Control bus -- Memory -- Time base -- Timing subsystem -- Port systems -- Analog-to-digital converters -- Communication systems -- Serial communications -- Terminology -- Serial communication signals -- Handshake mechanisms -- RS-232 protocol -- Interrupt system -- Speed -- Choosing a microcontroller for a specific design -- System requirements -- Microcontroller vendors -- Cutting edge technology -- Summary -- Timing subsystem -- Background theory -- Frequency -- Period -- Duty cycle -- Timer system -- Hardware -- Operation -- Applications -- Measuring external timing event -- Counting events -- Generating timing signals to interface external devices -- Industrial implementation case study (PWM) -- Summary -- Analog-to-digital conversion -- Background theory -- Analog signals versus digital signals -- Sampling, quantization, and encoding -- Resolution and data rate -- Analog-to-digital conversion process -- ADC conversion technologies -- Successive-approximation -- Integration -- Counter-based conversion -- Parallel conversion -- Applications -- Signal processing -- Signal conditioning for ATD converters -- Digital-to-analog conversion -- Industrial implementation: Digital cameras -- Summary -- Networked microcontrollers -- Background theory -- Designing computer networks -- Types of networks and protocols -- Microcontroller networks -- Controller area network -- BDLC networks -- Customized networks -- Applications -- Automobiles -- Mobile robots -- Summary -- Operating parameters and interfacing -- Operating parameters -- Input devices -- Switches -- Switch debouncing -- Keypads -- Sensors -- Output devices -- Light-emitting diodes (LEDs) -- Liquid crystal display (LCD) -- DC devices -- AC devices -- Application: DC motor speed and direction control -- Motor operating parameters -- Summary.
Includes bibliographical references and index.
Keywords: Microcontrollers